Analysis of Work Accidents in Drilling and Well Rework Activities in PT BCY's Rig Using Concepts Human Factor Analysis - Revi, Revi Adib Pramudita; Fatma, Fatma Lestari (Jurnal Kesmas Jambi, 2025)
Between 2019 and 2024, PT BCY recorded 26 reportable workplace incidents, including serious injuries and fatalities. This study aims to analyze the contributing factors to these incidents using the Human Factors Analysis and Classification System (HFACS). Employing a descriptive method, the study utilized 26 accident and near-miss reports. Incidents were categorized into four HFACS levels: unsafe acts, preconditions for unsafe acts, unsafe supervision, and organizational influences. The analysis identified 38 cases involving organizational influences, 36 involving unsafe supervision, 43 involving preconditions for unsafe acts, and 34 involving unsafe acts. Preconditions for unsafe acts were the most frequently identified contributing factor.